Book Review: Developing Rural School Leaders: Building Capacity Through Transformative Leadership Coaching - Ian M. Mette (Journal of Research in Rural Education, 2021)
How do we conceptualize the development of rural educational leaders? How do we ensure students living in rural America have access to world-class instruction in a complex and rapidly shifting world? What do we need to do differently to provide transformative educational experiences for rural teachers, students, and families? In Developing Rural School Leaders: Building Capacity Through Transformative Leadership Coaching, Klar and Huggins (2020) merge the best of theory and practice to create a framework for rural educational leadership development for both educational leadership preparation programs and for practicing rural school leaders. Their book provides a comprehensive educational leadership model with contextual applications, which helps to close the theory-practice gap that often plagues education.